Performance of International Growth References to Assess Nutritional Status in a Sample of Adolescents from Northeastern Brazil - De Moraes-Ferrari, G (Associacao Brasileira de Pos - Graduacao em Saude Coletiva, 2025)
This study aimed to assess the obesity diagnostic accuracy based on body fat mass (FM) in a sample of adolescents from northeastern Brazil, and to compare their nutritional status classified by the height and body mass index (BMI) references from the World Health Organization (WHO/2007), Centers for Disease Control And Prevention (CDC/2000), International Obesity Task Force (IOTF/2012), Brazil (2006) and MULT (2023). We selected 256 adolescents (10-19y) from the city of Natal, Brazil. Their nutritional status was classified according to the growth references and the obesity classification and the diagnostic accuracy were performed according to their FM, obtained through the Dual-energy X-ray absorptiometry (DXA). The Bland-Altman method was used to verify the concordan-ce among the growth references. The highest obesity prevalence (4.3%) was by applying WHO, CDC and Brazil and the highest critical difference (CD) was found between the BMI references of WHO and MULT (CD = 0.61). The MULT presented the highest values for sensitivity (0.98; 95%CI: 0.96-0.99) and positive likelihood ratio values (+LR) (4.88; 95%CI: 0.85-28.17). Therefore, it seemed to address contemporary growth trends, as it presented great accuracy for diagnosing obesity in this sample of adolescents from northeastern Brazil. © 2025, Associacao Brasileira de Pos - Graduacao em Saude Coletiva. All rights reserved.